Development of a Notification-Based Network Security Monitoring System Using Network Development Life Cycle (NDLC) - Butarbutar, Ryan Timothy Benget Daulat; Sasmita, Gusti Made Arya; Pratama, I Putu Agus Eka (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2023)
Developments in information and communication technology which are increasing rapidly, it is also required to improve the quality of security. The increase of internet usage has led to high number of intrusions or attacks that exploit weaknesses in internet protocols, operating systems and application software. Due to the high number of attacks, information technology security is an important thing to consider in an organization or individual. One solution that can be applied to overcome this problem is to monitor network security. One of the implementations of network security monitoring is the implementation of an Intrusion Detection System (IDS). The purpose of this research was to design a Snort-based network security monitoring system as a tool for implementing IDS to detect attacks by sending notifications via Telegram Bot which is integrated with the server owned by Unit Sumber Daya Informasi Universitas Udayana using the Network Development Life Cycle (NDLC) method. Based on the configuration results of research conducted on the Unit Sumber Daya Informasi Universitas Udayana server, there was the lowest data on May 16, 2023 with 64,418 data and the highest data on April 04, 2023 with 261,672 data and 2 Nmap Scan attack data as the lowest type of attack and 13,703 DDoS attack data as the highest type of attack.